2017
DOI: 10.1080/21645515.2016.1255388
|View full text |Cite
|
Sign up to set email alerts
|

Shedding of porcine circovirus type 1 DNA and rotavirus RNA by infants vaccinated with Rotarix®

Abstract: Thirty-three infants aged »2 months had serial stool samples collected after receipt of Rotarix Ò vaccine dose 1, and were assessed for shedding of porcine circovirus type 1 DNA and Rotavirus group A RNA by molecular methods. We did not find strong evidence that porcine circovirus type 1 replication occurred. Porcine circovirus type 1 genome with the same sequence as that in Rotarix Ò was detected in a few infants as late as day 13; while this timing could suggest there may have been replication and not just t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
0
6
1
Order By: Relevance
“…Rotavirus shedding was observed at any time frame in 23% and 47% of the infant vaccinated with Rotarix and RotaTeq, respectively, and only in 11% and 19% at ≥4 DPV. These are low vaccine shedding rates compared to previous studies in Taiwanese and North American infants 7,33 . A previous study from Malawi, also found relatively low shedding rates for Rotarix ≥4 DPV after first dose (30%).…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Rotavirus shedding was observed at any time frame in 23% and 47% of the infant vaccinated with Rotarix and RotaTeq, respectively, and only in 11% and 19% at ≥4 DPV. These are low vaccine shedding rates compared to previous studies in Taiwanese and North American infants 7,33 . A previous study from Malawi, also found relatively low shedding rates for Rotarix ≥4 DPV after first dose (30%).…”
Section: Discussioncontrasting
confidence: 66%
“…Bernstein and coworkers reported 70% shedding after first inoculation of the vaccine candidate 89-12, precursor of the Rotarix vaccine, in seronegative North American infants 5 . A more recent study in non-Hispanic North American infants showed that 79% of the Rotarix vaccinated infants shed the vaccine strain at >3 DPV 33 . These studies demonstrate a lack of rotavirus shedding in approximately 20–30% of seronegative infants vaccinated with Rotarix, suggesting that this subgroup was not susceptible to vaccination with P[8] rotavirus.…”
Section: Discussionmentioning
confidence: 99%
“…These children could be shedding vaccine strain after vaccination and illness is perhaps caused by other infectious pathogens or non-infectious aetiologies [41-43]. Furthermore, the high proportion of G1P[8] vaccine-derived strains may to some extent be the result of the increasing use of molecular methods in diagnostic laboratories across England; these methods will detect shedding of vaccine strain, potentially for months after vaccination, because of higher sensitivity compared with antigen detection methods [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, scientists from Northern Ireland, the United States, and Germany could not detect antibodies or antigens of PCV2 in human samples (56)(57)(58)(59). However, in other studies, antibody of PCV1 or antigen of PCV2 was detected in human sera, digestive tract samples and respiratory tract samples (60)(61)(62)(63)(64)(65). Although there is serological and molecular proof of PCV presence in humans, the detection rate is very low.…”
Section: Pcvs In Human Samplesmentioning
confidence: 99%